1998
DOI: 10.1007/bf01345278
|View full text |Cite
|
Sign up to set email alerts
|

Precursors of taurine in female genital tract: Effects on developmental capacity of bovine embryo producedin vitro

Abstract: Two precursors of taurine have been studied: cysteamine and hypotaurine. Cysteamine has been quantified in genital secretions and found in follicular fluids of all species tested. On the contrary cysteamine was not detected (or traces) in tubal fluids of the same species. Addition of 50, 100 or 250 microM of cysteamine to the maturation medium used in the culturing of bovine oocytes did not improve the cleavage rate nor the embryo's developmental potential in vitro. Furthermore, at 250 microM, cysteamine seems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 43 publications
0
20
0
2
Order By: Relevance
“…Large amounts of taurine and hypotaurine are present in gametes and in the embryo environment in all the species reported to date. The beneficial effect of supplementing culture medium with taurine on in vitro embryo development has been reported in several species, including the mouse (10), cow (11,12), and rabbit (13). It has been demonstrated that enriching the culture medium with taurine and melatonin can improve in vitro oocyte meiotic maturation and embryo development (14).…”
Section: Discussionmentioning
confidence: 99%
“…Large amounts of taurine and hypotaurine are present in gametes and in the embryo environment in all the species reported to date. The beneficial effect of supplementing culture medium with taurine on in vitro embryo development has been reported in several species, including the mouse (10), cow (11,12), and rabbit (13). It has been demonstrated that enriching the culture medium with taurine and melatonin can improve in vitro oocyte meiotic maturation and embryo development (14).…”
Section: Discussionmentioning
confidence: 99%
“…Instead, small molecule scavengers like vitamin C and vitamin E seem to play a more important role in the extracellular milieu. Significant amounts of CSH have been detected in the follicular fluid of the cow, sow, goat and dog [9].…”
Section: Introductionmentioning
confidence: 99%
“…The ROS generation may be from embryo metabolism or embryo surroundings (8,9). Although the embryo has several mechanisms of defense against ROS (10,11), rapid embryonic development continues to generate more ROS (4). The exact role of oxygen species in early embryonic development has yet to be fully identified.…”
mentioning
confidence: 98%